The language cliché in the modern informative broadcasting (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the communicative and pragmatic peculiarities of cliché as regular standardized stereotype units in language of the modern Ukrainian television media are being considered in particular.
Keywords: language cliché; communicative peculiarities; pragmatic peculiarities; discourse of media